Hubungan Pajanan Debu PM10 dan PM2.5 dengan Gangguan Pernapasan Pada Pekerja Penambang Batu Kapur Kabupaten Kebumen - Prasetyo Adi Nugroho; Onny Setiani; Yusniar Hanani (Postgraduate, University of Mataram, 2024)
Limestone mining activities have an impact on respiratory disorders among workers due to the presence of dust particles smaller than 10µ. Workers experiencing respiratory issues are at risk of occupational diseases, especially as limestone mining operations continue. The presence of particulates (PM2.5 and PM10) not only causes respiratory problems but also other health issues, as a large number of particulates entering the body over a long period can increase the risk of death. The purpose of this study is to analyze the relationship between exposure to PM10 and PM2.5 dust and respiratory disorders among limestone mining workers in Kebumen Regency. This study is an analytical observational study with a cross-sectional approach, involving a population of 62 workers spread across 11 locations. The results showed a relationship between work duration (p-value = 0.024), length of exposure (p-value = 0.007), smoking habits (p-value = 0.015), use PPE (p-value = 0.003), and disease history (p-value = 0.000) with respiratory disorders. Meanwhile, age, PM2.5, and PM10 levels did not show a relationship with respiratory disorders as the p-values were > 0.05. The variables predominantly associated with respiratory symptoms were work duration (OR=5.100), length of exposure (OR=22.277), completeness of PPE (OR=17.330), and disease history (OR=7.536). Conclusion this study that PM2,5 and PM10 do not have a significant relationship with respiratory disorders among limestone mining workers in Kebumen Regency.